PENGARUH PROFITABILITAS, TINGKAT PERTUMBUHAN DAN TINGKAT PAJAK TERHADAP STRUKTUR MODAL PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019 - Khadijah, Siti; Rozi, Facrul; Nursidin, Muhammad (Worksheet : Jurnal Akuntansi, 2023)
This study aims to analyze the specific effect of Asset Growth Rate, Tax Rate on Capital Structure inReal Estate and Property companies listed on the Indonesia Stock Exchange (IDX). The sample in thisstudy is 40 real estate and property companies that publish fully audited financial reports. The type ofdata used is secondary data obtained from the financial reports of each Real Estate and Propertycompany for 3 years, namely 2017-2019. Data analysis using multiple linear regression analysis. Theresults of this study indicate that the variable profitability (ROE) has a negative and significant effect onthe capital structure of Real Estate and Property. Meanwhile, the asset growth rate and tax rate have apositive and insignificant effect on the capital structure of Real Estate and Property companies